Ethiopian Digital Agro-Climate Advisory Platform (EDACaP) Improvement: Progress and Lessons - Ahmed, Jemal Seid; Sotelo, Steven; Tesfaye, Kindie; Tamene, Lulseged D.; Ramirez, Julian (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
Ethiopian agricultural production and productivity are strongly affected by weather and climate. Varying climatic conditions bring disparities in food demand and supply, which constitute a challenge for the integration of climate-smart agriculture in the agriculture mix. To help solve this problem, the AICCRA-Ethiopia project works on improving the Ethiopian Digital Agro-climate Advisory Platform (EDACaP) that, for the first time, integrates sub-seasonal to seasonal climate predictions and agronomic management options bundled with value chain actor technologies to enhance agricultural production and productivity demand. Together with national Research-Development institutions and agricultural extension users, AICCRA-Ethiopia has co-produced an operational Ago-climate service that will enable agricultural producers (farmers) and input providers (private sectors), extension officers and policymakers to design better-informed strategies in a few weeks and months in the future through the digitally enabled decision support system. Therefore, the overall scope and objective of this work, which is coordinated by CIMMYT in collaboration with the Alliance of Bioversity and CIAT and the Ethiopian Institute of Agricultural Research (EIAR), is to contribute to the improvement of Ethiopia’s Digital Agro-Climate Advisory Platform (EDACaP) through an overall backed and frontend software upgrading.